Evaluation effect of fresh potatoes included in a food based meal, on production and milk quality in Holstein cows - Fonseca-López, Dania Alejandra; Borras-Sandoval, Luis Miguel (Universidad Pedagógica y Tecnológica de Colombia, 2014)
Due to the increasing need to seek profitable feeding strategies for livestock that have good quality, and are of easy adoption, rose the idea of using crops by-products. In this work the effect of fresh potato waste on the production and quality of milk in 6 Holstein cows between first and second birth, with average yields of 24 L/cow/ day, which had more than 4 weeks breastfeeding was evaluated. It was worked under a completely randomized design with 2 treatments for the different percentages of inclusion of fresh potatoes, with three replicates each treatment, for a total of 6 experimental units, which were randomly divided in TC = 30 treatments % -35% + ms potato + balanced food in amount of 4.5 to, 4 kilos, T1 = 25% + ms of potato + balanced food in quantity needed to meet requirements + 100g protected fat; T2 = 20% more food potato + balanced food in the amount necessary to cover requirements + 200 g of protected fat. Significant differences were found: (p< 0.05) for T2 fat, with an increase of 1.61%, followed by the T1: 1.2%. The animals supplemented with T1 and T2 produced 0.6 and 1.7 L/day more milk compared with the control treatment, respectively. Applying the Tukey test was obtained that the best treatment was T2 with 4.92%, followed by T1: 4.46%, and the control (TC) 3.29%. For the protein, density and total solids variables, no statistically significant differences (p> 0.05) were found.